Answer:
![x_1=0\\ \\x_2=\pi](https://img.qammunity.org/2020/formulas/mathematics/college/v7tuadnyzdx83pd0b5yq3vq9kijc6k29lb.png)
Explanation:
Use definitions of
and
![\sec x:](https://img.qammunity.org/2020/formulas/mathematics/college/o2j65o6azob0xasvk6vt2gxnaomc48z2zp.png)
![\tan x=(\sin x)/(\cos x)\\ \\\sec x=(1)/(\cos x)](https://img.qammunity.org/2020/formulas/mathematics/college/mpvvuvg0bjetgx0k82sx6isyoydyfd02z3.png)
Hence, the equation is
![\left((\sin x)/(\cos x)\right)^2\cdot \left((1)/(\cos x)\right)^2+2\left((1)/(\cos x)\right)^2-\left((\sin x)/(\cos x)\right)^2=2](https://img.qammunity.org/2020/formulas/mathematics/college/inf2xb1q4ouc4yexgdkgg2hjudkubyn3gv.png)
Multiply this equation by
![\cos ^4x:](https://img.qammunity.org/2020/formulas/mathematics/college/q25a7f0z2ckot81kb1gnxc38hpvvtusoq9.png)
![\sin^2 x+2\cos^2 x-\sin^2x\cos^2x=2\cos^4x\\ \\\sin^2 x+2\cos^2 x-\sin^2x\cos^2x-2\cos^4x=0\\ \\\sin^2x(1-\cos^2x)+2\cos^2x(1-\cos^2x)=0\\ \\(1-\cos^2x)(\sin^2x+2\cos^2x)=0](https://img.qammunity.org/2020/formulas/mathematics/college/4lb1almp5n6y3hiudflftwssim2t6d92gn.png)
This means that
![1-cos^2x=0\ \text{or} \ \sin^2x+2\cos^2x=0](https://img.qammunity.org/2020/formulas/mathematics/college/npq3pt150jv9do5zxovlkkpf4twg0zzral.png)
The second equation has no solutions, because the sum of two non-negative numbers is 0 only if both these numbers are 0 and this is impossible, because
and
cannot be 0 simultaneously.
Solve the first equation:
![\cos^2x=1\Rightarrow \\ \\\cos x=1\ \text{or}\ \cos x=-1\\ \\x=2\pi k,\ k\in Z\ \ \text{or}\ \ x=\pi+2\pi k,\ k\in Z](https://img.qammunity.org/2020/formulas/mathematics/college/vj9xz0oeroewtqmpv33q05nro3oe2vxos8.png)
If
then
![x_1=0\\ \\x_2=\pi](https://img.qammunity.org/2020/formulas/mathematics/college/v7tuadnyzdx83pd0b5yq3vq9kijc6k29lb.png)